2020
DOI: 10.1108/jbim-09-2018-0280
|View full text |Cite
|
Sign up to set email alerts
|

The buyer–seller relationship: a literature synthesis on dynamic perspectives

Abstract: Purpose Contemporary scholars contend that the buyer–seller relationship is dynamic in nature, so it grows, matures and declines over time. However, most studies that adopt the dynamic perspective debates its conceptualization and how dynamic effects are captured. This scholarly discourse has led to multiple dynamic perspectives and resulted in fragmented and scattered literature on the subject. This study aims to synthesize the large body of research on dynamic perspectives in a systematic way. Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
1
21
0
1
Order By: Relevance
“…Its effect on sales performance is also greater than that of the level of commitment (Palmatier et al , 2013). In their study of the dynamic perspectives of buyer-seller relationships, Hussain et al (2020) identified the relationship velocity perspective. They found that the velocity perspective of buyer-seller relationship development can empower marketing managers to devise appropriate strategies to increase performance as relationships develop.…”
Section: Research Objectives and Research Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its effect on sales performance is also greater than that of the level of commitment (Palmatier et al , 2013). In their study of the dynamic perspectives of buyer-seller relationships, Hussain et al (2020) identified the relationship velocity perspective. They found that the velocity perspective of buyer-seller relationship development can empower marketing managers to devise appropriate strategies to increase performance as relationships develop.…”
Section: Research Objectives and Research Contributionmentioning
confidence: 99%
“…In particular, they focus on the rate and direction of change in commitment. Additional support for examining the impact of DT on the speed of relationship development is provided by psychological research, which indicates that people project trends and make decisions based on them (Johnson et al , 2005; Sahin et al , 2016; Hussain et al , 2020).…”
Section: Research Objectives and Research Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer-brand relationship is becoming the mainstay of marketing research (Centeno et al, 2019;Coelho et al, 2019;Hussain et al, 2020), where EBA helps brands to maintain sustainable relational bonds with customers (Torres et al, 2020). EBA is conceptualized as the emotion-laden relationship of consumers with the brand that minimizes their switching behavior (Torres et al, 2020;Vlachos et al, 2010).…”
Section: Emotional Brand Attachmentmentioning
confidence: 99%
“…Megatrend of digitalization has altered also buyer–seller relationships. Buyer–seller relationships, under different theoretical concepts such as relationships, channels, and supply chains, have been, and continue to be, one of the central areas of research in industrial marketing (Reid and Plank, 2000; Hussain et al , 2020). Several scholars have researched how different digital technologies and tools alter and influence different aspects of buyer–seller relationships (Mathews and Wilson, 1974; Stern and Kaufmann, 1985; Salo, 2012; Salo and Wendelin, 2013).…”
Section: Introductionmentioning
confidence: 99%